Beginning Swift games development for iOS : develop 2D and 3D games using Apple's SceneKit and SpriteKit - Goodwill, James; Matlock, Wesley (Apress, 2017)
Game apps are one of the most popular categories in the Apple iTunes App Store. In response, James Goodwill, Wesley Matlock and Apress introduce you to the update of this best selling book, Beginning Swift Games Development for iOS, Second Edition. In this book, you'll learn the fundamental elements of the new Swift 3 programming language as applied to game development for new iOS 10. What you'll learn Discover what's in the new Swift 3 programming language Apply Swift 3 to iOS 10 and 9 game development Build a 2D game app using SpriteKit and Swift Build a 3D game from 2D using SceneKit and Swift.